Basic Research on Oncofertility for Further Technological Innovation - Nao Suzuki (Fertility & Reproduction, 2023)
Background: As a result of “advances in Oncology” and “advances in Reproductive Medicine” in recent years, some cancer survivors have achieved live births after cancer treatment. The world’s first report on ovarian tissue cryopreservation (OTC) and thawed-ovarian tissue transplantation in young patients with Hodgkin’s lymphoma by Professor Donnez and colleagues in Belgium in 2004 was a breakthrough in this research field. On the other hand, the report on ovarian transplantation in humans by Dr. Morris in the United States in 1906, the success of frozen ovarian thawing and transplantation in rodents by Dr. Parrott in the United Kingdom in 1960, and the success of Dr. Gosden in England in OTC using the slow freezing method in large animals in 1994 were important research results that led to Professor Donnez’s success. The current standard technique for OTC is slow freezing, and many reports of live births have been obtained. However, further technological innovation is needed for further progress in Oncofertility. I will give a talk titled “Basic Research on Oncofertility for Further Technological Innovation” focusing on the research results of our institution. Methods: I report on the following research topics: 1) the establishment of the ovarian vitrification freezing method, 2) the ovarian toxicity of new molecularly targeted drugs, and 3) the detection of minimal residual disease (MRD). Results: 1) the establishment of the ovarian vitrification freezing method, 2) the ovarian toxicity of new molecularly targeted drugs, and 3) the detection of minimal residual disease (MRD). Results: The following research topics will be reported: 1) Successful establishment of ovarian vitrification freezing method, 2) Results on ovarian toxicity of molecularly targeted drugs (PARP Inhibitor), 3) Results on detection of MRD (minimal residual disease). Conclusions: Further technological innovation should be needed for further progress in Oncofertility for the CAYA cancer patients.